Temperature Effects on Biomass and Regeneration of Vegetation in a Geothermal Area - Nishar, Abdul; Bader, Martin K.-F.; O’Gorman, Eoin J.; Deng, Jieyu; Breen, Barbara; Leuzinger, Sebastian (Frontiers in Plant Science, 2017)
Understanding the effects of increasing temperature is central in explaining the effects of climate change on vegetation. Here, we investigate how warming affect vegetation regeneration and root biomass? and if there is an interactive effect of warming with other environmental variables? We also examine if geothermal warming effects on vegetation regeneration and root biomass can assist with climate change predictions? Monitoring plots were arranged in a grid across the study area to cover a range of soil temperatures. The plots were cleared of vegetation and root-free ingrowth cores were installed to assess above and below-ground regeneration rates. Temperature sensors were buried in the plots for continued soil temperature monitoring. Soil moisture, pH and soil chemistry of the plots were also recorded. Data were analysed using least absolute shrinkage and selection operator and linear regression to identify the environmental variable with the greatest influence on vegetation regeneration and root biomass. There was lower root biomass and slower vegetation regeneration in high temperature plots. Soil temperature was positively correlated with soil moisture and negatively correlated with soil pH. Iron and sulphate were present in the soil in the highest quantities compared to other measured soil chemicals and had a strong positive relationship with soil temperature. Our findings suggest that soil temperature had a major impact on root biomass and vegetation regeneration. In geothermal fields, vegetation establishment and growth can be restricted by low soil moisture, low soil pH, and an imbalance in soil chemistry. However, high temperatures appear to have the strongest control over plant growth. The correlation between soil moisture, pH, chemicals and temperature was explained by their common driver. Soil temperature was negatively correlated to the distance from the geothermal features. This study demonstrates a novel approach to global warming experiments, which could be particularly useful in low heat flow geothermal systems that more realistically mimic soil warming.